Diaphragmatic Pacing as an Alternative to Mechanical Ventilation: Early Experience from a Developing Country - A. S. Sardenberg, Rodrigo; N Younes, Riad (Journal of Respiratory Diseases, 2019)
Background The aim of this study is to evaluate the outcomes of patients submitted to diaphragmatic pacing, and the impact on quality of life of patients who chronically depend on mechanical ventilation, as well as the effectiveness of phrenic stimulation to eliminate the need for mechanical ventilation. Methods From 2010- 2014, 10 patients completely dependent on mechanical ventilation were operated upon, with the implantation of phrenic pacing device. The diagnoses were quadriplegia and congenital central hypoventilation syndrome (CCHS). All patients underwent bilateral approach to the phrenic nerves, by video-assisted thoracic surgery or mini-thoracotomy. Results All patientsstarted pacing 30-40 days post-operatively. The mean age of patients was 12.1 years (2-27 years range) with a median of ten years. Six patients (54.5%) were as old as ten years, and three (27.2%) were older than 20 years. Younger patients had CCHS and older ones were quadriplegic. All patients with CCHS (n = 4) were nine years old or younger while only two quadriplegic patients were in this age group. Conclusions Diaphragmatic pacing can provide improvement in the quality of life of patients who depend on mechanical ventilation, allowing freedom to conduct daily activities, lower respiratory infections, and tracheostomy decannulation.
Keywords: Diaphragmatic Pacing; Mechanical Ventilation; Phrenic; Quadriplegia; Congenital Central Hypoventilation Syndrome